2019
DOI: 10.1186/s12916-019-1328-3
|View full text |Cite
|
Sign up to set email alerts
|

Childhood generalized specific phobia as an early marker of internalizing psychopathology across the lifespan: results from the World Mental Health Surveys

Abstract: Background Specific phobia (SP) is a relatively common disorder associated with high levels of psychiatric comorbidity. Because of its early onset, SP may be a useful early marker of internalizing psychopathology, especially if generalized to multiple situations. This study aimed to evaluate the association of childhood generalized SP with comorbid internalizing disorders. Methods We conducted retrospective analyses of the cross-sectional population-based World Mental H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 47 publications
5
22
0
1
Order By: Relevance
“…The present study demonstrated that more than 5% of the studied schoolchildren had more than 5 types of phobia. This finding is supported by a study done by de Vries et al, 2019, who found that 8% of children reported four or more phobias [31]. The present study also scored the phobia into the low score (1-9) and high score (≥10) which accounted for 60.9% and 35.2%, respectively, of the studied participants.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present study demonstrated that more than 5% of the studied schoolchildren had more than 5 types of phobia. This finding is supported by a study done by de Vries et al, 2019, who found that 8% of children reported four or more phobias [31]. The present study also scored the phobia into the low score (1-9) and high score (≥10) which accounted for 60.9% and 35.2%, respectively, of the studied participants.…”
Section: Discussionsupporting
confidence: 90%
“…Most of the phobias generally appear in early childhood, the studied fifth or sixth graders (9-12 years) showed the highest percentage for almost all types of phobia because older children are more susceptible to phobia than younger children. With respect to phobias, our results are in agreement with Bener et al, 2011;Varughese and Peteru, 2019;and de Vries et al, 2019 suggesting that phobias were common in the age group 6-11 years [5], [26], [31]. Results of other studies were somewhat different from those found in our sample, two studies suggested that the average age of onset of phobias symptoms at approximately 8 years [11], [37].…”
Section: Discussionsupporting
confidence: 86%
“…For this purpose, finding the factors associated with increased risk for anxiety persistence is essential. A related question is whether predictors of anxiety disorder persistence manifest themselves differently in childhood than in adulthood (as early identification allows for prevention measures) 11 or have a more stable presentation across the lifespan.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that people with high symptom levels at the time of interview are more likely to recall symptoms experienced earlier in life, which could potentially lead to spurious associations between the latent trajectory classes and 12-month outcomes. We have previously found that associations between childhood specific phobia and lifetime outcomes were present among people with and without psychopathology at the time of interview (De Vries et al, 2019), suggesting that current symptomatology cannot fully explain the association between childhood symptoms and later outcomes. Prospective research has also found consistent associations between childhood-onset disorders and later outcomes (e.g.…”
Section: Strengths and Limitationsmentioning
confidence: 97%